Effects of chlorpyrifos-methyl and pirimiphos-methyl applied with 5°C temperature on Sitophilus oryzae (L.) (Coleoptera: Curculionidae) in wheat grain - Pražić Golić, Marijana; Andrić, Goran; Kljajić, Petar (Julius-Kühn-Archiv, 2018)
The effects of the insecticides chlorpyrifos-methyl and pirimiphos-methyl in combination with low temperature treatment at 5°C were tested in the laboratory to improve the existing pest management programs for S. oryzae control. Adults were released into wheat grain pretreated with three insecticide doses: 0.08, 0.12 and 0.16 mg/kg of chlorpyrifos-methyl, and 0.125, 0.19 and 0.25 mg/kg of pirimiphos-methyl, and exposed to 5°C temperature over intervals of 5, 6, 7 and 8 days. Mortality after low temperature only, insecticides only, and their combinations, was assessed after 1, 2, 7 and 14 days of recovery at 25±1°C and 60±5% r.h., as well as their impact on F1 progeny production/reduction (PR) after 8 weeks. The combined application of 0.16 mg/kg chlorpyrifosmethyl and 5°C temperature (5-7 days of exposure) caused a significantly higher mortality of S. oryzae after 1, 2, 7 and 14 days of recovery than the activity of low temperature alone, as well as the combined application of 0.12 mg/kg chlorpyrifos-methyl and 5°C after 7 and 14 days of recovery. Adults mortality and progeny reduction of S. oryzae was =92% after 14 days of recovery from an interaction of 0.16 mg/kg dose of chlorpyrifos-methyl and exposure for 6 days to 5°C, as well as all doses in combination with 7 days exposure to 5°C. Combined application of 0.25 mg/kg pirimiphos-methyl and 5, 6 and 7 days of exposure to 5°C caused a significantly higher mortality of S. oryzae after 7, 2 and 1 day of recovery, respectively, compared to temperature-only exposure. High mortality (91-95%) and progeny reduction >92% were caused by the same pirimiphos-methyl rate in combination with 6 and 7 days of exposure to 5°C after 7 days of recovery as the combination of 5, 6 and 7 days of exposure to 5°C after 14 days of recovery.